2013
DOI: 10.1021/nn404166q
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Properties of the Protein Corona Surrounding Nanoparticles for Tuning Payload Release

Abstract: We manipulate the passive release rates of DNA payloads on protein coronas formed around nanoparticles (NPs) by varying the corona composition. The coronas are prepared using a mixture of hard and soft corona proteins. We form coronas around gold nanorods (NRs), nanobones (NBs), and carbon nanotubes (CNTs) from human serum (HS) and find that tuning the amount of human serum albumin (HSA) in the NR-coronas (NR-HS-DNA) changes the payload release profile. The effect of buffer strength, HS concentration, and conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(108 citation statements)
references
References 31 publications
4
104
0
Order By: Relevance
“…Distinct configuration of the adsorbed protein was observed compared to the blurred ones in Fig. 2C and D, confirming the existence of stronger bindings and firmer adsorption of BSA onto the surface of CNTs with a smallerdiameter [15,16]. DLS measurements showed increased hydrated radius after adding the protein to CNTs (98.7-125 nm for <10 nm group, 145.3-171.7 nm for 10-20 nm group, and 203.1-219.8 nm for 20-40 nm group).…”
Section: Characterization Of Cnts and Their Complexes With Bsa Using supporting
confidence: 63%
“…Distinct configuration of the adsorbed protein was observed compared to the blurred ones in Fig. 2C and D, confirming the existence of stronger bindings and firmer adsorption of BSA onto the surface of CNTs with a smallerdiameter [15,16]. DLS measurements showed increased hydrated radius after adding the protein to CNTs (98.7-125 nm for <10 nm group, 145.3-171.7 nm for 10-20 nm group, and 203.1-219.8 nm for 20-40 nm group).…”
Section: Characterization Of Cnts and Their Complexes With Bsa Using supporting
confidence: 63%
“…On the other hand, recent studies have shown that the presence of a protein corona could enhance the drug delivery action of NPs, promoting high payloads. Cifuentes-Rius et al 33 have shown that the payload release profile of pre-formed NP-protein corona complexes (nanorods, gold nanobones, and carbon nanotubes) is strongly affected by different biological environments. 33 In particular, fluids rich of hard corona proteins promoted a faster release of the payload than those bearing soft corona proteins.…”
Section: Cobalt Ferrite (Cofe 2 O 4 )mentioning
confidence: 99%
“…Cifuentes-Rius et al 33 have shown that the payload release profile of pre-formed NP-protein corona complexes (nanorods, gold nanobones, and carbon nanotubes) is strongly affected by different biological environments. 33 In particular, fluids rich of hard corona proteins promoted a faster release of the payload than those bearing soft corona proteins. Here, we report a detailed study about the behaviour of MLs dispersed in serum upon exposure to a LF-AMF in order to understand how the magnetically triggered release is influenced by the interaction with serum proteins.…”
Section: Cobalt Ferrite (Cofe 2 O 4 )mentioning
confidence: 99%
“…These AuNPs display unique optical, mechanical, electrical and chemical properties, 3 which have been widely applied in catalysis, 4 surface enhanced Raman spectroscopy (SERS), 5 and nanomedicine. 6 In the area of nanomedicine they have been employed in light activated release of therapeutic payloads by NP heating, 7 and AuNP radiosensitization, which is a novel approach to enhance the ionising radiation dose in radiotherapy.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%